2019
DOI: 10.1111/inm.12659
|View full text |Cite
|
Sign up to set email alerts
|

Smoking‐related violence in a mental health setting following the implementation of a comprehensive smoke‐free policy: A content analysis of incident reports

Abstract: Smoke‐free policies in mental health settings are important to protect health but are often impeded by staff concerns that physical violence may increase. We aimed to address the literature gap about the frequency, nature, and management of physical violence in relation to smoking. We compared the antecedents and containment of smoking‐related incidents of physical violence over a two‐year period, (12 months when an indoor‐only smoke‐free policy was in place, followed by 12 months after a new comprehensive smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
7
0
2
Order By: Relevance
“…The discrepancy between the views of healthcare professionals about patients' needs further highlights the importance of supporting staff to practice Open access patient-centred care by asking about smoking status, providing salient advice and offering opt-out assistance that takes into account the patient's individual needs. 20 While participants in this study reported that it is mainly the nursing staff who address smoking with patients, all agreed that it should be everyone's responsibility. Non-clinical staff may have a role in advocating for the provision of smoking cessation care in hospitals, but the effectiveness of smoking cessation care in a clinical setting is associated with advice from clinical staff.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The discrepancy between the views of healthcare professionals about patients' needs further highlights the importance of supporting staff to practice Open access patient-centred care by asking about smoking status, providing salient advice and offering opt-out assistance that takes into account the patient's individual needs. 20 While participants in this study reported that it is mainly the nursing staff who address smoking with patients, all agreed that it should be everyone's responsibility. Non-clinical staff may have a role in advocating for the provision of smoking cessation care in hospitals, but the effectiveness of smoking cessation care in a clinical setting is associated with advice from clinical staff.…”
Section: Discussionmentioning
confidence: 86%
“…20 The authors noted that 'recognising the triggers to smoking-related violence is an essential first step to prevent and manage potential violence without recourse to containment interventions' (p.210). 20 Consequently, failure to adequately manage nicotine withdrawal may result in increased potential for patient aggression and violence. 27 The management of nicotine withdrawal within the context of supporting patients to meet smoke-free health service policies was not raised by participants, suggesting a lack of knowledge of the symptoms of nicotine withdrawal and their consequences in the inpatient setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of the study the authors worked in the 'Psychosis Theme' which aimed to help people who experience psychosis improve their physical health, by increasing access and uptake of evidence-based interventions to improve outcomes related to sedentary behaviours [19,20] and tobacco smoking [21,22]. Also integral to this work, we explored staff and organisational barriers to implementing tobacco dependence treatment interventions in mental health settings [21][22][23][24]. In preparation for future implementation work, we wanted to understand the barriers and facilitators to engaging in and with research, from the perspectives of clinicians and researchers.…”
Section: Study Contextmentioning
confidence: 99%